Comparison of 2,4-D Alone and 2,4-D–Kinetin Combination on Callus Formation in Apium graveolens and Mentha sp. - Rika Miftakhul Jannah (Hasanuddin University, 2025)
Celery (Apium graveolens L.) and mint (Mentha sp.) are economically important aromatic crops. However, their propagation through seeds and vegetative methods is often inefficient due to low seed viability, inconsistent germination, contamination risks, and poor plantlet uniformity. Therefore, this study assessed the response of two plant growth regulator formulations for callus induction in both species under in vitro conditions using a descriptive analysis. Two media treatments were tested: MD1 (Murashige and Skoog (MS) + 1.2 mg L-1 2,4-D) and MD2 (MS + 0.3 mg L-1 2,4-D + 0.5 mg L-1 kinetin). Observations were conducted on days 7, 14, 21, and 35 after induction (DAI) to assess explant survival, callus formation, and morphology. MD2 medium showed a tendency toward higher explant survival and greater callus formation percentages than MD1 in both species under the observed conditions. Callus initiation occurred between 7 and 14 DAI, with MD2 producing a greater proportion of viable and actively proliferating calli, predominantly characterized by friable-to-compact textures and lighter coloration. In contrast, explants cultured on MD1 exhibited a higher incidence of tissue browning and reduced callus viability, indicating the inhibitory effects associated with high auxin concentrations. These results suggest that a balanced auxin–cytokinin combination provides a more favorable hormonal environment for early callus induction than a single high-dose auxin treatment alone. Therefore, MD2 medium is recommended as an optimal formulation for early-stage callus induction in celery and mint, with potential applications in micropropagation.